Boosted Membrane Potential as Bioenergetic Response to Anoxia in Dinoroseobacter shibae - Kirchhoff, Christian; Cypionka, Heribert (Frontiers in Microbiology, 2017)
Dinoroseobacter shibae DFL 12T is a metabolically versatile member of the world-wide abundant Roseobacter clade. As an epibiont of dinoflagellates D. shibae is subjected to rigorous changes in oxygen availability. It has been shown that it loses up to 90% of its intracellular ATP when exposed to anoxic conditions. Yet, D. shibae regenerates its ATP level quickly when oxygen becomes available again. In the present study we focused on the bioenergetic aspects of the quick recovery and hypothesized that the proton-motive force decreases during anoxia and gets restored upon re-aeration. Therefore, we analyzed ΔpH and the membrane potential (ΔΨ) during the oxic-anoxic transitions. To visualize changes of ΔΨ we used fluorescence microscopy and the carbocyanine dyes DiOC2(3) (3,3'-Diethyloxacarbocyanine Iodide ) and JC-10. In control experiments the ΔΨ-decreasing effects of the chemiosmotic inhibtors CCCP (carbonyl cyanide m-chlorophenyl hydrazone), TCS (3,3',4',5-tetrachlorosalicylanilide) and gramicidin were tested on D. shibae and Gram-negative and -positive control bacteria (Escherichia coli and Micrococcus luteus). We found that ΔpH is not affected by short-term anoxia and does not contribute to the quick ATP regeneration in D. shibae. By contrast, ΔΨ was increased during anoxia, which was astonishing since none of the control organisms behaved that way. Our study shows physiological and bioenergetical aspects comparing to previous studies on transcriptomic responses to the transition from aerobic to nitrate respiration in D. shibae. For the lifestyle as an epibiont of a dinoflagellate, the ability to stand phases of temporary oxygen depletion is beneficial. With a boosted ΔΨ, the cells are able to give their ATP regeneration a flying start, once oxygen is available again.